Relative price effects of monetary policy shock in Malaysia: a SVAR study - Zaidi, Mohd. Azlan Shah; Abdul Karim, Zulkefly; Wan Ngah, Wan Azman Saini (Faculty of Economics and Business, Universiti Malaysia Sarawak, 2016)
Studies on Malaysia monetary policy mostly examine the effect of monetary policy change on output and inflation in aggregate terms. While sectoral output effects of monetary policy have also been investigated, there is however a lack in the study on the effect of policy change on disaggregated inflation. This paper attempts to examine the later issue by employing structural vector autoregressive (SVAR) model. By estimating the model separately for each sub-group of Malaysian consumer price index, we find that a modest monetary policy shock results in varying degree of responses in disaggregated inflation. In other words, some sub-group inflation react instantly while others respond sluggishly to a monetary policy shock. In contrast to aggregate inflation response, there is also evidence of price puzzle. The results give some insight to monetary authority on how to control inflation in aggregate as well as in disaggregate terms and in turn manage the cost of living issues in Malaysia.